Effects of agro-forestry systems on the physical and chemical characteristics of green coffee beans - Xu, Su; Liu, Yuze; Sun, Zhenchun; Chen, Guangjing; Ma, Fengwei; Yang, Ni; de Melo Virginio Filho, Elias; Fisk, Ian D. (Frontiers in Nutrition, 2023)
Twenty agroforestry systems consisting of different management practices (conventional and organic) and shade types were set up for coffee plantations in 2000 at the Tropical Agricultural Research and Higher Education Center (CATIE), Turrialba, Costa Rica. The physical (density, bulk density, moisture content, and roasting loss) and chemical attributes (mineral, total lipid, fatty acids, caffeine, and carbohydrate contents) of harvested green coffee beans were investigated. The full sun and Erythrina shade tree systems significantly improved (p < 0.05) the density of the green coffee beans and decreased (p < 0.05) the moisture content and roasting loss of the green coffee beans.The intensive organic (IO) management practice significantly increased some mineral contents, such as K, P, and Ca, in the green coffee beans. The full sun system also significantly promoted (p < 0.05) some mineral contents, such as Ca and Mn, in green coffee beans. In terms of total lipid and fatty acids (FAs), compared with the moderate conventional (MC) management practice, the IO management practice was beneficial as it significantly increased (p < 0.05) the total lipid and FAs contents in the green coffee beans, while the Erythrina shade tree system significantly increased (p < 0.05) the total lipid and FAs contents of green coffee beans more efficiently than the other shade types. The caffeine content of green coffee beans was significantly higher (p < 0.05) under the intensive conventional (IC) and IO management practices than under the MC management practice and higher under the full sun system than under the shaded system. The Erythrina shade tree system significantly improved (p < 0.05) the carbohydrate content of green coffee beans. Overall, in consideration of sustainability, the IO management practice associated with the Erythrina shade tree system would be a useful combination for the local farmers to grow coffee trees.